Effectiveness Of Tajin Water (Rice-Water) As A Coupling Food To Improve Weight Board (Mus Musculus) - Lusi Agus Setiani; Moerfiah Moerfiah; Putri Kemala Dewi (Universitas Pakuan, 2023)
Malnutrition can occur on children of aged 6 to 24 months. During this period, there is generally a change in needs from exclusive breastfeeding to complementary foods and additional food can also be added. Starch water which is a springy white liquid obtained from rice that is cooked with the nutritional content of energy, protein, fat, carbohydrates, calcium, iron, vitamin B1. This study aims to test the effectiveness, determine the best concentration and determine the influence of the length time from using of starch water as an additional complementary food to increase body weight of male mice (Mus musculus) for 21 days by oral treatment. The experiment and method that used in this experiment is was pretest-posttest control group design. Starch water is obtained by means of rice being heated with 1200 mL of water for ± 30 minutes, filtering and extracting is obtained. Starch water concentrations commonly used empirically tested in this study are concentrations of 12.5%; 18.7%; 25%. The 25% concentration is the concentration that has an effective effect on body weight of mice with the results (21.87 ± 4.29) which differ 2.38% from the positive control results (24.25 ± 8.93).